Analysis of Needs And Distribution of Public Senior High Schools in Bandar Lampung City - Permatasary, Nayla Alviani; Firdaus, Rangga; Fitri, Dina Martha (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to determine the spatial distribution of public high schools in Bandar Lampung City, the needs of public high schools in Bandar Lampung City based on the Regulation of the Minister of National Education No. 24 of 2007, and the accessibility of public senior high schools with settlements according to the standards of the Minister of National Education of the Republic of Indonesia No. 24 of 2007. The research method used is descriptive method. The data analysis used is descriptive with secondary data analysis techniques. The population in this study were all State Senior High Schools in the city of Bandar Lampung, namely 17 school units. Data collection techniques used in this study are surveys and documentation. The results of the study found that the overall distribution of public high school locations in Bandar Lampung City was not evenly distributed. Public High School in Bandar Lampung City based on the standards of the Minister of National Education of the Republic of Indonesia No. 24 of 2007 according to Permendiknas is that at least one sub-district has one school unit with a minimum of 3 study groups and a maximum of 27 study groups, so for sub-districts that do not have public high schools, new school units are required to be built. Based on the threshold theory, the availability of educational facilities in Bandar Lampung City is still low. The accessibility of the school-age population to get education based on the zoning radius of 3 km is quite even.edu